ON DOUBLE NEW INTEGRAL TRANSFORM AND DOUBLE LAPLACE TRANSFORM - Kashuri, Artion; Fundo, Akli; Liko, Rozana (European Scientific Journal, ESJ, 2013)
In this paper, a relationship between double new integral transform and double Laplace transform was establish and many other results are presented. In this paper is considered general linear telegraph equation with constant coefficients and wave equation (Hassan Eltayeb et al., 2010) (Tarig. M. Elzaki et al., 2012). The applicability of this relatively double new integral transform is demonstrated using some special functions, which arise in the solution of PDEs. First, we transform the partial differential equations to algebraic equations by using double new integral transform method and second, using the inverse double new integral transform we get the solution of PDEs.